2020
DOI: 10.1111/jvh.13399
|View full text |Cite
|
Sign up to set email alerts
|

Loss to follow‐up in the hepatitis C care cascade: A substantial problem but opportunity for micro‐elimination

Abstract: | on behalf of the HepNed study group This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Yet, there was a subsequent drop in the cascade of care with treatment being completed in 90% of those who initiated. This finding is not surprising and consistent with the broader HCV literature among PWID where rates of loss to follow‐up or DAA treatment discontinuation have been reported in 5%–10% 11,16,47 . Treatment uptake was also higher than reported from mobile HCV clinics in Brisbane, Copenhagen and Madrid 32,35,37 .…”
Section: Discussionsupporting
confidence: 87%
“…Yet, there was a subsequent drop in the cascade of care with treatment being completed in 90% of those who initiated. This finding is not surprising and consistent with the broader HCV literature among PWID where rates of loss to follow‐up or DAA treatment discontinuation have been reported in 5%–10% 11,16,47 . Treatment uptake was also higher than reported from mobile HCV clinics in Brisbane, Copenhagen and Madrid 32,35,37 .…”
Section: Discussionsupporting
confidence: 87%
“…LTFU at different stages of hepatitis C care is a major barrier in controlling HCV infection globally. [17] Timely treatment of hepatitis C reduces the risk of cirrhosis, hepatocellular carcinoma, and death [36, 37]. Therefore, LTFU from hepatitis C care can increase the risk of adverse health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The cascade starts with hepatitis C antibody testing and ends with the determination of cure based on sustained virologic response (SVR) at 12 weeks after treatment completion [7][8][9][10][11][12][13][14][15][16]. Available data has found that loss to follow-up (LTFU) at different stages of the hepatitis C care cascade is common [17]. In 2019, globally, only 26% of people living with hepatitis C knew their infection status, and only 16% were treated [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, strategies that use automatic reflex viral load testing of specimens found positive for HCV antibodies may be associated with reduced losses at these testing steps [ 42 ]. Other countries have productively addressed HCV care continuum gaps and have tested and implemented more efficient approaches [ 47 , 48 ]. Similarly, recently studied and implemented interventions for HIV have focused on condensing the steps in the HIV continuum of care and include rapid, same-day initiation of ART [ 49–53 ], and bundled HIV/HCV testing [ 54–56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study’s high retention rates speak positively to participants’ adherence to study visits and thus suggest the need to further address structural and systemic issues that are complex and difficult to overcome even with a CF. These factors would include long waiting times, medication costs, social service needs (eg, unstable housing), and policies requiring sobriety that may serve as formidable barriers to forward movement along the HCV and HIV care continua [ 14 , 15 , 47 ].…”
Section: Discussionmentioning
confidence: 99%